2016
DOI: 10.3390/v8110311
|View full text |Cite
|
Sign up to set email alerts
|

Studies in a Murine Model Confirm the Safety of Griffithsin and Advocate Its Further Development as a Microbicide Targeting HIV-1 and Other Enveloped Viruses

Abstract: Griffithsin (GRFT), a lectin from Griffithsia species, inhibits human immunodeficiency virus-1 (HIV-1) replication at sub-nanomolar concentrations, with limited cellular toxicity. However, in vivo safety of GRFT is not fully understood, especially following parenteral administration. We first assessed GRFT’s effects in vitro, on mouse peripheral blood mononuclear cell (mPBMC) viability, mitogenicity, and activation using flow-cytometry, as well as cytokine secretion through enzyme-linked immunosorbent assay (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…Inhibitors of NiV entry and spread generally target protein interactions involved in receptor binding or membrane fusion processes [5][6][7][8][9][10], but the glycosylation of NiV glycoproteins presents another viable target for therapeutic development [11][12][13]. Griffithsin (GRFT) is a homodimeric high-mannose oligosaccharide binding lectin currently being evaluated in clinical trials as a topical microbicide against human immunodeficiency virus 1 (HIV-1) [14,15], and it has also demonstrated in vivo broad-spectrum activity against viruses including severe acute respiratory syndrome coronavirus, hepatitis C virus, and Japanese encephalitis virus [16][17][18][19]. In this study, we characterized the in vitro antiviral activities of GRFT and its synthetic trimeric tandemer (3mG) [20] against NiV and other viruses from 4 virus families, and tested the in vivo prophylactic potential of 3mG and an oxidation-resistant form of GRFT (Q-GRFT) against lethal NiV challenge in the Syrian golden hamster model.…”
mentioning
confidence: 99%
“…Inhibitors of NiV entry and spread generally target protein interactions involved in receptor binding or membrane fusion processes [5][6][7][8][9][10], but the glycosylation of NiV glycoproteins presents another viable target for therapeutic development [11][12][13]. Griffithsin (GRFT) is a homodimeric high-mannose oligosaccharide binding lectin currently being evaluated in clinical trials as a topical microbicide against human immunodeficiency virus 1 (HIV-1) [14,15], and it has also demonstrated in vivo broad-spectrum activity against viruses including severe acute respiratory syndrome coronavirus, hepatitis C virus, and Japanese encephalitis virus [16][17][18][19]. In this study, we characterized the in vitro antiviral activities of GRFT and its synthetic trimeric tandemer (3mG) [20] against NiV and other viruses from 4 virus families, and tested the in vivo prophylactic potential of 3mG and an oxidation-resistant form of GRFT (Q-GRFT) against lethal NiV challenge in the Syrian golden hamster model.…”
mentioning
confidence: 99%
“…Besides, GRFT shows superior stability, remaining functionally stable at 80 ℃ [5], and when exposed to repeated lyophilization [25], organic solvents and proteases [24]. Researchers have confirmed that GRFT has an outstanding safety profile with little toxicity or deleterious immunological consequences [10,11], which provides further evidence in support of the clinical application of GRFT.…”
Section: Introductionmentioning
confidence: 84%
“…It proved 50-fold less cytotoxic than cyanovirin, and it did not increase the level of activation markers in CD4 + T lymphocytes. Scalable manufacture of cyanovirin 19 and griffithsin 20 and validation of the safety and antiviral efficacy of griffithsin in mice and rabbits as a topical microbicide has been reported by O'Keefe et al, 21,22 Takebe et al, 23 Kouokam et al, 24 Farr Zuend et al 25 and Girard et al 26 Interestingly, Castillo-Acosta et al 27 recently demonstrated that Pradimicin, a mannosespecific agent purified from Actinomyces madura, can cure mice suffering from acute sleeping sickness caused by trypanosomes. 16 It induces only minimal changes in secretion of inflammatory cytokines and chemokines by epithelial cells and human PBMCs, does not markedly upregulate T cell activation markers and gene expression, and has no measurable effect on cell viability.…”
Section: Introductionmentioning
confidence: 90%